Pemenuhan Hak Bagi Masyarakat Adat Oleh Negara Di Bidang Hutan Adat - Muhammad Risky Surya Pratama; Arum Ayu Lestari; Rimas Intan Katari (Fakultas Hukum Universitas Islam Indonesia, 2022)
The purpose of this research is firstly, to examine the applicability of the Forestry Law in fulfilling the right to prosperity for indigenous peoples as regulated in Article 33 paragraph (3) of the 1945 Constitution of the Republic of Indonesia. Second, as a material for evaluation and recommendation of the Forestry Law so that the state can provide protection for the prosperity of indigenous peoples. The research method used is a normative research with statutory and case approaches. The results of the study conclude that first, in reality the Government has made regulations relating to the protection of the prosperity of indigenous peoples, both in terms of personal and material assets, especially cultural forests. However, there are still many policies from officials and individuals that are not in accordance with the regulations that have been enacted. Such as the case regarding land conflicts in the Pubabu Cultural Forest in Linamnutu Village. Second, there is still a need to expand the scope of legal assistance for indigenous peoples. Decisions regarding the status of cultural forests should not be viewed solely from administrative interests. This status must be seen from the perspective of human rights, especially the perspective of economic, social and cultural rights. In addition, the phrase